Exposure to Metals Can Be Therapeutic - Davey, Curt A (Chimia, 2015)
Because of the widespread epigenetic changes ensuing from carcinogenesis, structural and chemical features of chromatin provide unique targets for developing safer and more effective anticancer drugs. Metal-based agents have a potential advantage over other small molecular species in that characteristics of coordination geometry, redox state and ligand exchange allow one to fine-tune reactivity and affinity properties in a distinct fashion. This intersection of chromatin biology and bioinorganic medicinal chemistry is the subject of multiple collaborations in and between Switzerland and Singapore.